An overview of the low temperature microgravity physics facility capabilities - Pensinger, J.F.; Croonquist, A.P.; Liu, F.C.; Larson, M.E.; Chui, T.C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The Low Temperature Microgravity Physics Facility currently in the design phase is a multiple user and multiple flight facility intended to provide a long duration low temperature environmentonboard the International Space Station. The Facility will provide a unique platform for scientific investigations requiring both low temperature and microgravity conditions. It will be attached to the Japanese Experiment Module`s Exposed Facility and can house two science instruments each flight. The Facility consists of a 180-liter superfluid helium dewar, a support enclosure, and control electronics. The facility will be launched full of cryogen, and retrieved after the cryogen is depleted. Industrial partners are responsible for building the reusable facility and standard parts ofthe instruments. Principal Investigators from universities and other institutions are contracted to develop major parts of the science instrument package. An overview of the detailed technical capabilities of the facility will be presented in this paper.